Inheritance and allelic relationship of foliar blast resistance gene(s) in pearl millet - M, MALLIK; SINGH, S P; PRAKASH, G; SANKAR, S MUKESH; SINGHAL, TRIPTI; SUNDER, D SHYAM; R, THRIBHUVAN; SINGH, NIRUPMA; SATYAVATHI, C TARA (The Indian Journal of Agricultural Sciences, 2021)
Foliar blast disease in pearl millet (Pennisetum glaucum (L.) R. Br.) caused by Magnaporthe grisea once considered as a minor disease, has become major threat for pearl millet cultivation during recent decade in almost all pearl millet growing areas. The present study is an attempt to understand the inheritance of foliar blast resistance in pearl millet against the natural inoculum of Magnaporthe grisea and also against artificial inoculum of its devastating strain PMg_DI. The experiment was conducted at ICRISAT, Hyderabad and IARI, New Delhi during 2017-19. F2 and backcross populations derived from a susceptible genotype ICMB 95444 and two resistant lines PPMI-10018 and PPMI-2464 were used. Screening of individual plant in F1s, F2s, BCP1s (susceptible parent × F1) and BCP2s (resistant parent × F1) under field and controlled conditions indicated that the resistance is governed by a single dominant gene. The test of allelism was conducted by crossing the resistant parents. No segregation for resistance was observed in F2 generation when screened against the natural inoculum of Magnaporthe grisea and its strain PMg_DI. This indicates that both the resistant parents possess the same gene.